PREVALENCE OF TUBERCULOSIS, DRUG-RESISTANT TUBERCULOSIS AND HIV/TB CO-INFECTION IN ENUGU, NIGERIA. - Ugwu, Kenneth Okonkwo; Agbo, Martina Chinonye; Ezeonu, Ifeoma Maureen (African Journal of Infectious Diseases (AJID), 2021)
Background: Tuberculosis (TB) remains a global public health problem, with developing countries bearing the highest burden. Nigeria is first in Africa and sixth in the world among the countries with the highest TB burden, but is among the 10 countries accounting for over 70% of the global gap in TB case detection and notification. Enugu State, Nigeria reportedly has a notification gap of almost 14,000 TB cases; a situation which must be addressed. Methodology: A total of 868 individuals accessing DOTS services in designated centres within the six Local Government Areas (LGAs) of Enugu North geographical zone, were recruited into the study. The participants were screened for HIV seropositivity by standard protocols, while screening for TB and drug-resistant TB were conducted by a combination of Zhiel Neelsen staining and Nucleic Acid Amplification Test (Xpert® MTB/Rif). Results: Of the 868 subjects that participated in the study, 176 (20.3%) were HIV seropositive. The highest prevalence (26.7%) of HIV was recorded in Udenu LGA, while the least (13.1%) was recorded in Nsukka LGA. Overall TB prevalence was found to be 22.1% and 21.3% by sputum-smear and NAAT, respectively. Uzo Uwani LGA recorded the highest prevalence of both TB (33.3%) and TB/HIV co-infection (16.7%), but the lowest prevalence of resistant TB. Nsukka LGA had the highest prevalence of resistant TB. Conclusion: Enugu North geographical zone, Nigeria, has a high prevalence of both HIV and TB, including resistant TB and there is need to increase monitoring of this region.